ANALISIS KEBIJAKAN ANTI KEMISKINAN DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN DI KOTA MEDAN - Nasution, Amalia; Putri, Amanda Afriza; Trikania, Dinda; Ritonga, Rizka Sabila; Salsabila, Tri Utami; Wulandari, Sari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to analyze the policies implemented by the government to alleviate poverty in Medan and evaluate their effectiveness. The research employs a qualitative approach with descriptive analysis of secondary data from official documents, government reports, and related literature. The findings indicate that various policies, such as social assistance programs, job training, and community empowerment, have yielded positive impacts. However, challenges in implementation, such as unequal distribution and lack of community participation, remain significant obstacles. Recommendations are provided to enhance stakeholder synergy and leverage technology in the distribution of aid programs.